Impacto temporal desencadeado pela dieta básica regional sobre a barreira epitelial intestinal em modelo In vivo - Ribeiro, Samilly Albuquerque (2017)
Malnutrition is still a reality in regions of low socioeconomic power, such as the North and Northeast regions of Brazil. The understanding of the pathophysiologies triggered by multideficient diets is important for application of suitable treatments. The present study aimed to characterize the dynamic changes in the gastrointestinal barrier of mice malnourished by the regional basic diet (RBD), a diet typical of the brazilian semiarid region. Male C57BL/6 mice (21 days old) were induced to DBR malnutrition for a total period of 21 days. The bioelectrical impedance, the tail length, the morphometric evaluation and intestinal permeability (lactulose and mannitol test), gene transcription and protein expression of tight junctions, transmembrane transporters and CFTR were evaluated on the 7th, 14th and 21st days. The RBD significantly reduced (P<0.001) weight and weight gain from the 7th day, as well as reduced body mass values (P<0.05), total body fluid (P<0.01) and extracellular fluid (P<0.05). Intracellular fluid decreased (P<0.05) in the malnourished group only at 14 days, while fat mass decreased (P <0.05) in the 14th. The RBD altered the intestinal morphology of jejunum, with a significant reduction of the crypt height (P=0.002) and a significant increase of the villus/crypt ratio (P=0.049) on 7th; reduction of villi (P=0.022) and crypt (P=0.007) height on 14th; and a reduction of the crypt (P=0.001) and the villus/crypt ratio (P=0.012) on day 21. In L/M, there was significant reduction of both lactulose (P=0.004 and P=0.015) and mannitol (P=0.02 and P=0.031) in malnourished animals at the 7th and 14th experimental days and an increase in the L/M ratio (P=0.0317) in malnourished animals on the 14th. The levels of claudin-1 and occludin mRNA were reduced (P<0.05) in the malnourished group on day 14, while claudin-2 and occludin levels were reduced (P<0.05) at the 21st day. DBR increased levels of PepT-1 (P <0.05) in the 7th, SGLT-1 levels in the 7th and 14th (P <0.05) day, whereas, CFTR and SGLT-1 reduced (P <0.05) on the day 21. Protein expression was increased only to occludin in malnourished animals (P <0.05) on the 14th day. The DBR was capable of malnourish weanling mice, reducing weight gain, lean mass, fat mass and body fluids, as well as dynamically change the intestinal morphology of the jejunum, intestinal permeability and mRNA levels of tight junctions, intestinal transporters and chloride channel.